2017
DOI: 10.11648/j.ejpm.20170505.12
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Self-Medication with Antibiotics for Children in Makkah, Saudi Arabia

Abstract: Self-medication with antibiotics is becoming a very common practice, and it is being practiced globally carrying a significant economic burden and health hazards. This study assesses prevalence and predictors of self-medication with antibiotic for children. A cross-sectional study was carried out on 252 mothers selected randomly from primary health care Centers in Makkah, during the period Jan -July 2016. Mothers were interviewed about giving their children antibiotic without prescription using a semi structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Moreover, this study aimed to compare findings with previous findings from 2006 using similar methods and measures. The prevalence of self‐medication with antibiotics in this present study (40.4%) was comparable with our previous study (39.5%) in 2006, 13 and other studies conducted in Saudi Arabia 39.3%, 21 Sudan 41%, 22 United Arab Emirates, 23 Spain 41%, 12 Greece 44.6%, 24 Lithuania 45% 25 and Eritrea 45.1% 26 …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, this study aimed to compare findings with previous findings from 2006 using similar methods and measures. The prevalence of self‐medication with antibiotics in this present study (40.4%) was comparable with our previous study (39.5%) in 2006, 13 and other studies conducted in Saudi Arabia 39.3%, 21 Sudan 41%, 22 United Arab Emirates, 23 Spain 41%, 12 Greece 44.6%, 24 Lithuania 45% 25 and Eritrea 45.1% 26 …”
Section: Discussionsupporting
confidence: 90%
“…Penicillins, primarily amoxicillin and amoxicillin/clavulanic acid, were the most commonly used antibiotics in the self‐medicated group in our study. Amoxicillin and amoxicillin/clavulanic acid was most self‐medicated antibiotics in our previous study, 13 and many other studies, such as in Saudi Arabia, 21,30,31 Sudan, 22,28 Eritrea, 26 United Arab Emirates, 23,32 Yemen 36 and Greece 24 . Those medications are commonly prescribed for common illnesses such as respiratory tract infection and other types of infections, 37,38 and patients would store these medications for future use for similar conditions 9 .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We also found that most of the self-prescribed antibiotics were obtained from pharmacists (62.9%) and chemists (18.9%). This is similar to the study by Enas et al in Saudi Arabia which reported that 53.6% of self-prescribed antibiotics were obtained from pharmacies [ 30 ]. These similarities could be attributed to a lack of or inadequately implemented policies on antibiotic use or misuse which are common in low–middle-income settings.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, self-medication cannot be regarded as a completely safe action, rather it has potential risks, including misdiagnosis, increased use of medications, long-term use of medication, drug interference (13,14), delay in the search for appropriate treatment and medical advice, use of an unnecessary high dose of medication, presentation of rare, but serious and dangerous side effects, incorrect treatment selection, masking serious diseases, risk of dependence and drug abuse, resistance to antibiotics, and increased health costs due to an increase in mortality rates and increased length of hospitalization that can be problematic in some vulnerable groups, including the elderly (15). In various studies, numerous factors have been introduced to predict self-medication behaviors, including age, sex (7), marital status, depression, activity limitation, life satisfaction (10), education level, income level, place of residence and awareness level (16), past experiences of selfmedication and self-assessment of health status (17), cost saving (18), smoking and alcohol drinking, chronic illness, self-efficacy, and low drug literacy (17). Health literacy is associated with the ability of individuals to acquire, understand, and use information for health promotion (19), the situation that happens during the self-medication process according to most researchers; therefore, it seems that health literacy level is a determining factor in the occurrence of self-medication behaviors (20,21).…”
Section: Introductionmentioning
confidence: 99%